Innovations in sustainable energy and cleaner environment - Gupta, Ashwani. K. [ed.]; De, Ashoke [ed.]; Aggarwal, Suresh K. [ed.]; Kushari, Abhijit [ed.]; Runchal, Akshai [ed.] (Singapore Springer, 2020)
This book covers the state-of-the-art advances in several areas of energy, combustion, power, propulsion, and environment, focusing on the use of conventional and alternative fuels. It presents novel developments in the areas of biofuels and value added products from various feedstock materials, along with thermal management, emission control and environmental issues from energy conversion. Written by internationally renowned experts, the chapters in this volume cover the latest fundamental and applied research innovations on cleaner energy utilization for a wide range of devices extending from micro scale energy conversion to hypersonic propulsion using hydrocarbon fuels. The book will be useful as a ready reference for managers and practicing and research engineers, as well as graduate students and research organizations and institutions.
Keywords: Green energy; Renewable and Green energy